Electromagnetic properties and shapes of ground states in Pt-Au-Hg region - Rikovska, J; Wyss, R; Semmes, P (Kluwer Academic Publishers, 1992)
We present a comprehensive calculation of odd-A isotopes of Pt, Au and Hg in the mass region 177≤A≤195. Two nuclear models have been used. The particle-triaxial rotor model with modified oscillator s.p. potential (PTR-MO) yielded deformation parameters ε2 and γ as a result of fitting to a wide range of experimental data. Also, mean field calculations based on the Woods-Saxon potential with Strutinsky shell corrections were performed to predict deformation parameters β2, β4 and γ form Total Routhian Surfaces (TRS). Subsequent PTR calculation using these deformation parameters and Woods-Saxon s.p. potential (PTR-WS) yielded ground state properties of all nuclei in question in very good agreement with experiment. The deformation parameters ε2 and β2 showed the same general trend as a function of neutron number. The fitted parameter γ from (PTR-MO) calculation indicated a smooth change from prolate (N≈100) to oblate shape (N≈115) via triaxial in Pt, Au and Hg. The value of γ extracted from TRS calculations predicts a smooth change in Pt isotopes but much sharper change in Au and Hg nuclei. © 1992 J.C. Baltzer A.G., Scientific Publishing Company.